Students’ response towards synchronous game-based learning / Hanani Ahmad Zubir and Azila Azmi - Ahmad Zubir, Hanani; Azmi, Azila (Universiti Teknologi MARA, 2021)
Game-based learning has emerged as an active learning technique over the years from traditional to digital. In the light of coronavirus disease (COVID-19), Hospitality and Tourism to You (Ht2U) games which started as a book, followed by traditional board games which then went online through a website, have recently been incorporated through the Jamboard, a Google feature attached to Google Meet. This paper aims to study the students’ feedback on the latest form of the games in meeting the needs arising from the pandemic. The results highlight the characteristics of a good game extended by the online teaching and learning approach. It is hoped that future studies will lead to the expansion of online synchronous features that are predominantly suitable for vocabulary games